Food safety policy framework for Kenya: Lessons and best practices from the Vietnam experience - Kang'ethe, Erastus K.; Muriuki, Samuel; Karugia, Joseph T.; Guthiga, Paul M.; Kirui, Leonard (International Livestock Research Institute, 2020)
Infographic created for Voice for Change Partnership, Food and Nutrition Security Dissemination Forum: Evidence for Policy, Advocacy and Partnerships, Online Webinar, 8th July 2020